Increasing the nonlinear character of microbubble oscillations at low acoustic pressures. - Stride, E; Pancholi, K; Edirisinghe, M; Samarasinghe, S (2008)
The nonlinear response of gas bubbles to acoustic excitation is an important phenomenon in both the biomedical and engineering sciences. In medical ultrasound imaging, for example, microbubbles are used as contrast agents on account of their ability to scatter ultrasound nonlinearly. Increasing the degree of nonlinearity, however, normally requires an increase in the amplitude of excitation, which may also result in violent behaviour such as inertial cavitation and bubble fragmentation. These effects may be highly undesirable, particularly in biomedical applications, and the aim of this work was to investigate alternative means of enhancing nonlinear behaviour. In this preliminary report, it is shown through theoretical simulation and experimental verification that depositing nanoparticles on the surface of a bubble increases the nonlinear character of its response significantly at low excitation amplitudes. This is due to the fact that close packing of the nanoparticles restricts bubble compression.